(untitled) (Linguostylistic Studies, 2017)
The article reveals the key factors that affect the etiquette language behavior of the addressee in friendly correspondence. The emphasis is laid on the addressee’s factor which is considered as dominating in this context. The author places importance on the etiquette units, the formation of which is influenced by the personality of the addressee and which are important elements in the structural and compositional organization of the epistolary text. The article analyzes typical for the Ukrainian epistolary tradition and individual author’s constructions, the choice of which depends on the addressee.